Ta’tsīr Isti‘khdām Wasīlah Wordwall wa Quizizz ‘alā Natā’ij Ta‘līm al-Mufradāt fī al-Madrasah al-‘Āliyah al-Ḥukūmiyyah 1 Bādang - Roza, Ellia; Faisol, Yufni; -, Rahmawati (Al-Uslub: Journal of Arabic Linguistic and Literature, 2025)
The vocabulary mastery of students at MAN 1 Kota Padang is relatively low. This issue is attributed to the lack of variety in instructional media, which diminishes students' motivation to learn. Therefore, engaging learning media such as Wordwall and Quizizz are needed to improve vocabulary learning outcomes. This study aims to investigate the effect of using Wordwall and Quizizz on students' vocabulary learning outcomes. A quantitative approach with an experimental method was employed. The research sample consisted of two classes: an experimental class using Wordwall and Quizizz, and a control class that did not use these media. Data were collected through observation and tests. Data analysis included normality tests, homogeneity tests, and hypothesis testing using a t-test. The results showed a t-value of 3.416 with a significance level of 0.001, which is less than 0.05. This indicates that the alternative hypothesis (Ha) is accepted, demonstrating a significant effect of using Wordwall and Quizizz on students' vocabulary learning outcomes at MAN 1 Kota Padang. Thus, Wordwall and Quizizz are proven to be effective in enhancing students' vocabulary learning outcomes. Keywords: Arabic Learning, Quizizz, Vocabulary, Wordwall